2017
DOI: 10.1097/bot.0000000000000825
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Associated With High Perioperative Complications Among Surgically Treated Intertrochanteric Fracture of the Femur

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 23 publications
2
29
0
2
Order By: Relevance
“…Consistent with previous studies, obese patients who sustained fractures were found to be signifi cantly more likely to have increased hospital lengths of stay [6,7,23,[25][26][27][28], more frequent admissions to the ICU and longer associated lengths of stay in the ICU [6,13,28,29]. Furthermore, after adjusting for The authors noted that the study was underpowered to detect a statistical difference between these two groups in terms of pulmonary complications, multiple organ failure and mortality [6].…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with previous studies, obese patients who sustained fractures were found to be signifi cantly more likely to have increased hospital lengths of stay [6,7,23,[25][26][27][28], more frequent admissions to the ICU and longer associated lengths of stay in the ICU [6,13,28,29]. Furthermore, after adjusting for The authors noted that the study was underpowered to detect a statistical difference between these two groups in terms of pulmonary complications, multiple organ failure and mortality [6].…”
Section: Discussionsupporting
confidence: 77%
“…Esse estudo indicou ainda que pacientes com IMC maior ou igual a 40 apresentaram taxas muito maiores de complicações respiratórias (18%) e de feridas do que os outros obesos e não obesos. 16 Com base nas taxas maiores de complicações, um estudo aponta que a taxa de óbito foi o dobro entre os pacientes com obesidade mórbida (IMC igual ou superior a 40), em comparação aos não obesos, o que é possível correlacionar com as comorbidades associadas à obesidade, como diabetes, disfunção cardíaca e pulmonar, maior incidência de trombose venosa profunda, infecções cirúrgicas, hérnia incisional, entre outros. 3,4,17 No presente trabalho, houve aumento no número de óbitos com menção de ambas as causas, que quase dobrou de 2004 para 2014.…”
Section: Discussionunclassified
“…Interrogation of the Veterans Affairs Surgical Quality Improvement Program (VASQIP) database showed that in total joint arthroplasty, a BMI > 40 kg/m 2 is an independent predictor for superficial infection. 181 Similarly, obese patients undergoing open reduction and internal fixation of distal humeral fractures or total elbow arthroplasty 132 total ankle arthroplasty or ankle arthrodesis, 131 total shoulder arthroplasty 133 fixation for intertrochanteric femur fractures, 182 and fixation of a fracture of an ankle 183 all have an increased incidence of surgical-site infections when compared to non-obese patients undergoing the same surgery.…”
Section: Wound Infectionmentioning
confidence: 99%